Assessing clinical preventive health care services of The University Health Centre, International Islamic University, Malaysia by analysing its electronic medical record data to improve care services - Tin, Myo Han; Abdullah, Fa’iza; Thuraiapprah, D. M. (2011)
A university health center is an ideal setting to study the services provided in primary care. Analysis of electronic medical record (EMR) data of such a university health center supports to get more understanding on patients and practice environments that can be used to set improvement of health care services.